KAJIAN PRASARANA PENDIDIKAN SEKOLAH DASAR SEBAGAI SALAH SATU INDIKATOR PENCAPAIAN STANDAR NASIONAL PENDIDIKAN - Sari, Yulia Ratna; M, Yoko Masna Rivan. (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aimed to study the level of achievement of primary school infrastructure standards in Banjarmasin City. This method of the research was intended to obtain data of the achievement of educational infrastructure. Results of the study showed that the level of achievement of primary school infrastructure reached 60,94%. This level of achievement still seems to be low partly due to the lack of insfrastructure which is still owned by the school. In addition, although the school already has the infrastructure of education, the quality conditions of many infrastructures suffered heavy damage so it unfit for use. Types of infrastructure its educational echievement is higher than average includes: classroom, the boardroom, the teachers’s room, and playground. On the contrary, the educational infrastructure is below average achievement including: school’s health unit, library, and restroom. The conclusion of this study is that the achievement of educational infrastructure in Banjarmasin city has not met the requirements of education national standards.